Fostering Multimodal Literacy through Creative English Songwriting Activities - Patty, Jusak; Lekatompessy, Felicia Miranda; Lekatompessy, Jeny (Journal of Community Service and Society Empowerment, 2026)
Many EFL students spend years studying English without ever feeling confident enough to actually use it. This community service program at SMP Negeri 49 Maluku Tengah sought to address that gap by introducing creative English songwriting to build multimodal literacy among 40 eighth-grade students. The program ran across four stages: listening to and discussing selected English songs, writing original lyrics collaboratively in small groups, transforming those lyrics into complete musical compositions using Suno AI, and presenting the finished work to peers. Data were gathered through direct observation and reflective documentation throughout each session. Findings showed that students engaged with English more actively and more personally than conventional classroom tasks typically allow. The listening stage drew sustained attention from students who normally disengage during text-heavy instruction. The songwriting stage generated genuine collaboration and purposeful language use. The AI audio stage produced curiosity and investment that carried through to the final presentation. Students did not just practice English; they used it to make something. These findings suggest that multimodal songwriting activities can offer EFL learners a qualitatively different relationship with the language, one grounded in creative expression rather than academic compliance.